Integralisme Islam dan Kontribusi Budaya Muakhi Bagi Peradaban Masyarakat Serta Relevansi Nilai-Nilai Filosofis Budaya Lokal dan Pembangunan Masyarakat Lampung - Nurdin, A. Fauzie (AL-ADYAN, 2019)
This study reveals and explains about 'Islamic Integralism and the Contribution of Muakhi Culture to World Civilization, which is focused on the relevance of the philosophical values of Local Culture and Lampung Community Development'. The problems are: (1) Are Islamic values integrated with the philosophical values of the local culture as a philosophy of life for the people of Lampung ?; (2) How is the nature of Islamic values integrated with Lampung culture in relation to the life cycle of humans, nature and the environment; (3) How are the philosophical values of local culture (muakhi) relevant to the development of Lampung society. The research aims to uncover and explain the three problems scientifically, objectively, philosophically and academically. The philosophical approach is used to explain problems that must be "understood" and actualized in everyday life. The method used is involved observation, in-depth interviews, and documentation study. Qualitative analysis in the field of philosophy is carried out by interpreting, interpreting, comparing and linking the theory of "Islamic Intergralism and Muakhi Culture" with data that has been processed, criticized and can be applied. The result turns out that Islamic integralism and muakhi culture based on the philosophical values of Lampung's local culture are reality and the work of the perpetrators, so Piil Pesenggiri as a philosophy of life grows and muakhi culture develops in society as a 'local genius' and 'local wisdom' of the nation that is useful for community development and world civilization. The findings of the research, namely: First, Islamic integralism - based on the philosophical values of Muakhi culture as the philosophy of life of indigenous peoples - can contribute to the development of Lampung society. Second, the essence of Islamic values integrated with the life cycle of humans, nature and the environment in the Lampung regional development relations manifests in the development of whole people based on faith, good deeds and virtues that have values for the welfare of society and world civilization in the future. Third, the philosophical values of local culture (muakhi) have relevance and can contribute positively and significantly to the development of Lampung society.